The Effectiveness of the Group Investigation-Type Cooperative Model Assisted by Folklore-Based Teaching Materials in Understanding Story Content - Andi Muhammad Ridwan; Firdaus (Journal of Primary Education Innovation and Research, 2025)
This study aims to determine the effectiveness of the Group Investigation-type Cooperative Learning Model assisted by folklore-based teaching materials on the story content comprehension ability of third-grade students at SD Inpres 12/79 Iterrung. This study employed a One-Group Pretest-Posttest Design, with the population consisting of all third-grade students and a sample of 28 students selected using a saturated sampling technique. The instruments used included multiple-choice tests to measure students’ story content comprehension ability before and after the implementation of the learning model, a questionnaire to measure students’ responses, and an observation sheet to assess the implementation of learning. The data were analyzed descriptively and inferentially. The results of the analysis showed that the mean Pretest score was 44.29, while the mean Posttest score was 77.32. The average student response questionnaire score was 91.07%, and the implementation of learning was categorized as highly implemented. The Kolmogorov-Smirnov normality test indicated that the data were normally distributed, and Levene’s homogeneity test showed that the data were homogeneous. The results of the t-test showed that the calculated t-value (18.476) > the t-table value (1.70329), indicating that H0 was rejected and H1 was accepted. Therefore, it can be concluded that the Group Investigation-type Cooperative Learning Model assisted by folklorebased teaching materials is effective in improving the story content comprehension ability of third-grade students at SD Inpres 12/79 Iterrung.